1992
DOI: 10.1111/j.1365-2273.1992.tb01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in immunologic response in tonsillectomized children. I Immunosuppression in recurrent tonsillitis

Abstract: The possible immunoregulatory role of the tonsils was studied by determining immunoglobulins IgG, A, M, E and factors C'3, C'4 and PFB of the complement system before and after tonsillectomy. The synthesis in vitro of IgG and IgM by lymphocytes stimulated with pokeweed mitogen was also measured. There were statistically significant differences between pre and post-operative levels of serum IgG, IgA and IgM, which decreased after surgery. Practically no change in the mean values of IgE and no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…It is speculated that tonsillectomy negatively affect the immune system in children. On the other hand, many studies indicate that tonsillectomy seems to have no counterproductive effect on the immune system [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…It is speculated that tonsillectomy negatively affect the immune system in children. On the other hand, many studies indicate that tonsillectomy seems to have no counterproductive effect on the immune system [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…But another study 7 has shown higher serum of IgA, IgG and IgM level in patients before operation than that of the control group. Sainz et al (1992) 8 in Spain and Lal et al (1984) 9 in India also reported increased level of IgG, IgM and IgA in patients with chronic tonsillitis than that of control group. In the present study before tonsillectomy among the patients with tonsillar disease, serum IgG level was slight higher while IgM, IgA levels were slight lower compared to group B.…”
Section: Discussionmentioning
confidence: 95%
“…After studying 53 children 3-4 yrs after tonsillectomy, LENANDER-LUMIKARI et al [22] suggested that the surgery did not weaken the humoral immune status of human saliva. Other researchers even suggested that tonsillectomy may improve the immune response [23]. Further studies are warranted to determine immunological mechanisms of predisposition to respiratory illness after T/A in response to ETS exposure.…”
Section: Discussionmentioning
confidence: 99%